Effect of Family-Centered Nursing-Based Health Education on Activities of Daily Living among Elderly Hypertensive Patients in Indonesia: A Quasi-Experimental Study - Suprayitno, Emdat; Hannan, Mujib; Hidayat, Syaifurrahman; Permatasari, Dian; Huzaimah, Nailiy (Chakra Brahmanda Lentera Institute, 2025)
Background: Hypertension is a common chronic condition in the elderly, leading to decreased independence in performing Activities of Daily Living (ADL). Family support is a key determinant in maintaining the independence of the elderly. However, the family's role is still not optimal. Health education based on family-centered nursing (FCN) is expected to empower patients and families to manage hypertension and improve functional abilities. Methods: A quasi-experimental design with a non-equivalent control group was applied to evaluate the effect of Family-Centered Nursing (FCN)-based education on Activities of Daily Living (ADL) among elderly hypertensive patients. 64 participants meeting the inclusion criteria were selected using simple random sampling from the Rubaru Community Health Center, Indonesia. Data were collected using the validated Barthel Index questionnaire and analyzed with the Wilcoxon and Mann–Whitney tests using SPSS version 25. Results: Based on the paired t-test, the daily living activities score, p-value <.001, and the Independent test, p-value < .001 was obtained for both the control and treatment groups. This demonstrates the influence of family-centered nursing education on the independence of daily living activities of hypertension sufferers in the work area of the Rubaru Community Health Center. Conclusion: Family-centered nursing education has an impact and is effective on the daily living activities of older people with hypertension in the Rubaru Community Health Center (Puskesmas) area. It is recommended that the Community Health Center integrate family-based education programs into routine health services for the elderly.